Employee innovation in the context of strategic change implementation in the service sector - Erić Nielsen, Jelena; Vidosavljević, Julija; Boškovic, Nikola (Hotel and Tourism Management, 2024)
Purpose – The purpose of this paper is to determine whether variables – managerial support for innovative ideas, work autonomy, rewards/reinforcements, time availability, organizational barriers, and specific parameters of organizational climate, have an impact on the organizational performance of employees in the service sector of the Republic of Serbia. Additionally, the study will investigate whether there are differences in the perceptions of employees depending on their positions within the organization. Methodology – The sample consists of 105 participants. The study applied reliability analysis, correlation analysis, multiple regression analysis, and the T-test for two independent samples. Findings – Results indicate that managerial support, work autonomy, time availability, organizational barriers, and specific parameters of organizational climate positively influence the organizational performance of employees in companies that have undergone an organizational change process, while rewards/reinforcements do not have an impact. Implications – Meetings should be held to outline how innovations will be assessed, given the significant impact of management support on organizational performance. To enhance employee performance, it is advisable to align the reward system with innovative behavior by offering additional rewards for successfully implemented innovations. Moreover, establishing an “innovation budget” can provide employees with the necessary resources, thereby nurturing a culture of innovation within the organization.